The Protection of the Environment: Protection of Health and Food Safety- EU and Serbia - Sič, Magdolna (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
From the beginning of the last century the process of harmonization and unification of the law on food safety for the protection of consumers in the European Union (EU) is ongoing. According to these rules, participants in the production and distribution of food have to respect the rules in all phases of production: ‘From Farm to Fork’. Honoring of the rules is based on self-control and the responsibility of producers and distributors, and is subject to public control with appropriate sanctions by competent authorities of a Member State as well as the EU. In the Republic of Serbia, after singing the Stabilization and Association Agreement, the statutory law has been approximated with the laws of the EU. That however, is not sufficient. It is necessary to develop the self-control of producers as well as to organize an efficient public control, not only because this is a necessary condition for export of food products to the single market of the EU, or for the membership in the EU, but also for ensuring safe food in the internal market of Serbia.